Odpowiedzi

2010-03-10T16:02:27+01:00
A)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x= 5/8

b)-7(x-2)=3x-1

-7x+14=3x-1
-7x-3x=-1-14
4x=-15 / :4
x= - 15/4
c)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5
2 4 2
2010-03-10T16:03:34+01:00
A)5x+2=7-3x / +3x ; -2
8x = 5 /÷8
x = ⁵₈

b)-7(x-2)=3x-1
-7x + 14 = 3x -1 / -3x ; -14
-13x = -15 / ÷ (-13)
x = 1 ²/₁₃

c)4(x-1)=6(1+x)
4x -4=6+ 6x /+4 ; -6x
-2x = 10 / ÷ (-2)
x = - 5
2 4 2
2010-03-10T16:04:08+01:00
A)5x+2=7-3x
5x-3x=2+7
2x=8 /:2
x=4
c)4(x-1)=6(1+x)
4x-4=6+6x
4x+6x=4+6
10x=10x /:10
x=1
2 4 2